The crystal structure of 1-ethyl-2-nitro-imidazole oxide, C5H7N3O3 - Jun Yuan; Bingheng Wu; Yong Wang; Jianlong Wang; Duanlin Cao; Lizhen Chen (Zeitschrift für Kristallographie - New Crystal Structures)
C5H7N3O3, monoclinic, P21/n (no. 14), a = 8.7821(7) Å, b = 7.1320(5) Å, c = 11.6293(10) Å, β = 104.718(3)∘ $104.718{(3)}^{° }$ , V = 704.49(10) Å3, Z = 4, Rgt ${R}_{gt}$ (F) = 0.0468, wRref $wR_{ref}$ (F 2) = 0.1125, T = 170.0 K.